PENGEMBANGAN LKPD BIOLOGI BERORIENTASI HOTS BERBASIS PBL PADA MATERI VIRUS - Sri Wahyuni; Anisa; Irmawanty (STKIP Subang, 2025)
Sri Wahyuni. 2025. Development of HOTS-Oriented Biology Student WorksheetBased on PBL on Virus Material for Class X MAN Kepulauan Selayar. Thesis.Biology Education Study Program, Faculty of Teacher Training and Education,Muhammadiyah University of Makassar. Supervisors: Anisa (Supervisor I) andIrmawanty (Supervisor II). This study aims to create a HOTS-focused and PBL-based Biology Student Worksheet for high school students, especially on the topicof viruses. The background of this study shows a lack of variation in learningmethods, the application of biology lessons that are not optimal in everyday life,and low active participation in the learning process at MAN Kepulauan Selayar.The methodology applied in this study is the Research and Development (R&D)approach using the ADDIE model, which consists of five main stages: Analysis,Design, Development, Implementation, and Evaluation. The resulting product is aprinted LKPD designed with the Canva platform and can be accessed via a link orQR code. The validity of this LKPD has been evaluated by experts in the field ofmaterials and media, who gave validity scores of 3.9 and 4 respectively, falling intothe category of "very valid". The practicality test was conducted by a teacher and31 grade X students, with the results showing a practicality level of 100% from theteacher (very practical category) and 85% from the students (very practicalcategory). These findings indicate that the LKPD can be a good alternative as abiology learning tool, because it not only supports students understanding ofscientific concepts, but can also encourage the development of other teachingmaterials, such as LKPD based on Problem-Based Learning which focuses onhigh-level thinking skills (HOTS), especially in the context of biological materialssuch as viruses.